Adult congenital cardiac life-long needs evaluation in a low-middle income country, Pakistan - Laila Akbar Ladak; Disty Pearson; Kathy Jenkins; Muneer Amanullah; Waris Ahmad; Kaitlin Doherty Schmeck; Amy Verstappen; Babar Sultan Hasan (Journal of the Pakistan Medical Association, 2020)
Abstract Objective: Adult congenital heart diseases (ACHD) have distinct health care needs that require life-long care. Limited data is available from low-middle income countries (LMIC). This descriptive study conducted in Pakistan aimed to assess patients and health care professionals understanding of the needs for ACHD care and the perceived barriers to care. Methods: A telephone survey was conducted of ACHD patients. An e-mail survey was sent to the pediatric and adult cardiologists of five institutions (3 public and 2 private) that provide ACHD services in Pakistan. Descriptive statistics (frequencies, mean ± SD, median) were used for data analysis. Results: A total of 128 ACHD patients were surveyed, 65 (51%) were females with a mean age of 29.4±10.4 years. Atrial septal defect repair was the most common surgical procedure. Mean age at surgery was 25.6±10.49 years, and a surgical follow-up period of 3.8±2.3 years. Majority (n=3, 60%) of the health care professionals (HCPs) responded that 75-100% of the ACHD surgical patients would need lifelong care, yet 10-25% return to their cardiology clinics. Most of the surveyed ACHD patients (89%, n=114) demonstrated a lack of understanding of life-long care after surgery due to not being communicated by their HCPs. Cost and travelling issues were the barriers highlighted by HCPs. Both ACHD patients (96%, n=122) and HCP (100%, n=5) underscored their interest in life-long care. Continuous......